Hàn Mặc Tử và nhóm thơ Bình Định - Nguyễn, Toàn Thắng. (Hà Nội : Nhà xuất bản Giáo dục, 2007)
Criticism of Vietnamese literature.
Includes bibliographical references (p. 330-333)
Keywords: Authors, Vietnamese -- 20th century -- History and criticism; Vietnamese literature -- History and criticism